World War I - Murphy, Donald J. 1936- (Turning points (Greenhaven Press), 2002)
This book is a collection of essays on World War I, discussing the potency of nationalism, the horrific conditions of trench warfare, the nations' casualties, and the weaknesses of the peace settlement.